Optimal scheduling model for integrated energy systems in parks considering multi-energy - Li, Peng; Tian, Chunzheng; Li, Huixuan; Zhang, Yihan (2022 7th Asia Conference on Power and Electrical Engineering (ACPEE), 2022)
The integrated energy system of the park is characterised by diverse load demands and complex energy supply equipment. In order to reduce the construction and operation costs of multiple energy sources in the integrated energy system of the park and to solve the problems of high energy operation costs and unreasonable cost structure in the energy supply of the integrated energy system of the park, an optimal scheduling method of the integrated energy system of the park considering multiple energy coupling is proposed. Firstly, the operating costs of four energy sub-systems, namely electricity, heat, cooling and gas, are specified; then, the objective function of minimising the construction and operating costs of the integrated energy system in the park is solved using Matlab by considering various constraints; finally, the proposed method is validated by using an industrial park in northern China as a simulation object. The results show that the proposed optimal scheduling method can effectively reduce the operating cost of the park and optimise the output structure of each unit.